Generational Dynamic Convergence as a Mechanism for Reducing Intergenerational Friction - Rendy Soewitoardjo; Thomas Stefanus Kaihatu; Christian Herdinata (Politeknik Siber Cerdika Internasional, 2026)
Background: As organizations play to the strength of generational diversity while working through challenges towards productivity and cohesion, generational diversity is a two-edged sword in the contemporary multigenerational workplace. Objective: This study seeks to create and validate the Generational Dynamic Convergence (GDC) construct that establishes the level of multigenerational diversity so as to diminish intergenerational friction and improve organizational performance in family-owned business in Surabaya, Indonesia. Methods: GDC encompasses four interconnected dimensions based on theories of social behavior, organizational culture, and generational identity: Environmental Perception, Innovation Implementation, Generational Inclusion, and Communication Styles. The reliability and relevance of the GDC dimensions are validated by an Exploratory Factor Analysis (EFA) of data from 120 family-owned businesses in Surabaya, Indonesia. Results: Results indicate that GDC has the ability to bridge the generational gap, promote cooperation, and can be the solution to generational friction by harnessing the respective strengths of Baby Boomers, Generation X, Millennials, and Generation Z and can, as such, serve as a catalyst in creating inclusive, adaptable, resilient, and high-performing organizational cultures. This can be avoided in future consideration as the framework can be extended to different geographical and organizational contexts, making the results and conclusions more generalisable and useful. Conclusion: This research is the first to both identify and validate the GDC construct through EFA and in doing so reveals four distinct dimensions of GDC and show that generational convergence can enhance collaboration, innovation and performance and simultaneously reduce intergenerational conflict.